Identifying hub genes in response to ustekinumab and the impact of ustekinumab treatment on fibrosis in Crohn’s disease - Xu, Ying; Wang, Shu; Ye, Ziping; Zhang, Hongjie (Frontiers in Immunology, 2024)
Crohn’s disease (CD) is a chronic inflammatory disease. About 50% of CD patients progressed from inflammation to fibrosis. Currently, there are no effective drugs for treating intestinal fibrosis. Biologic therapies for CD such as Ustekinumab have benefited patients; however, up to 30% of CD patients have no response to initial treatment and the effect of Ustekinumab on intestinal fibrosis is still uncertain. Therefore, it is of great significance to explore the predictive factors of Ustekinumab treatment response and the effect of Ustekinumab on intestinal fibrosis. GSE207465 , GSE112366 and GSE207022 were downloaded and analyzed based on the treatment response. Differentially expressed genes (DEGs) were identified by “limma” R package and changes in immune cell infiltration were determined by “CIBERSORT” R package at week 0. To find predictive factors of Ustekinumab treatment response, the weighted gene co-expression network analysis (WGCNA) R package was used to identify hub genes in GSE112366. Hub genes were then verified in GSE207022, and a prediction model was built by random forest algorithm. Furthermore, fibrosis related gene changes were analyzed in ileal samples before and after treatment with Ustekinumab. Our analysis found that MUC1, DUOX2, LCN2 and PDZK1IP1 were hub genes in GSE112366. GSE207022 revealed that MUC1 (AUC:0.761), LCN2 (AUC:0.79) and PDZK1IP1 (AUC:0.731) were also lower in the response group. Moreover, the random forest model was shown to have strong predictive capabilities in identifying responders (AUC=0.875). To explore the relationship between intestinal tissue and blood, we found that ITGA4 had lower expression in the intestinal and blood samples of responders. The expression of IL18R1 is also lower in responders’ intestines. IL18, the ligand of IL18R1, was also found to have lower expression in the blood samples from responders vs non-responders. GSE112366 revealed a significant decrease in fibrosis-related module genes and fibrosis-related pathways after Ustekinumab treatment. MUC1, LCN2 and PDZK1IP1 were identified as hub genes in intestinal samples, with lower expression indicating a positive prediction of Ustekinumab treatment response. Moreover, ITGA4 and IL18/IL18R1 may be involved in the treatment response in blood and intestinal samples. Finally, Ustekinumab treatment was shown to significantly alter fibrotic genes and pathways.